2010
DOI: 10.1890/09-1218.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influences on population dynamics: evidence from an exploited freshwater fish

Abstract: We used a field experiment, population modeling, and an analysis of 30 years of data from walleye (Sander vitreus; a freshwater fish) in Lake Erie to show that maternal influences on offspring survival can affect population dynamics. We first demonstrate experimentally that the survival of juvenile walleye increases with egg size (and, to a lesser degree, female energy reserves). Because egg size in this species tends to increase with maternal age, we then model these maternal influences on offspring survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 69 publications
3
127
1
Order By: Relevance
“…Other studies have also documented a stock effect on walleye egg size (Johnston, 1997;Johnston and Leggett, 2002;Moles et al, 2008) and egg quality (Czesny et al, 2005). However, previous studies investigating linear relationships between walleye maternal traits and egg size point to inconsistent relationships, with some studies indicating that larger females produce larger eggs (e.g., Johnston, 1997;Wiegend et al 2007;Moles et al, 2008;Venturelli et al, 2010), while studies of other stocks suggest no such relationship (Czesny et al, 2005;Moles et al, 2008;present study).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Other studies have also documented a stock effect on walleye egg size (Johnston, 1997;Johnston and Leggett, 2002;Moles et al, 2008) and egg quality (Czesny et al, 2005). However, previous studies investigating linear relationships between walleye maternal traits and egg size point to inconsistent relationships, with some studies indicating that larger females produce larger eggs (e.g., Johnston, 1997;Wiegend et al 2007;Moles et al, 2008;Venturelli et al, 2010), while studies of other stocks suggest no such relationship (Czesny et al, 2005;Moles et al, 2008;present study).…”
Section: Discussionmentioning
confidence: 58%
“…Because of the relationships between maternal characteristics and egg size, changes in average maternal characteristics within a stock may affect mean egg size and have consequences for population dynamics. For example, size-selective harvesting may truncate female age and length distributions, leading to a decrease in mean egg size and quality Bobko and Berkeley, 2004), which could ultimately compromise recruitment potential and thereby affect population dynamics (e.g., Venturelli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most fish species, larger eggs and larvae with increased lipid reserves are considered higher quality (Brooks et al 1997;Venturelli et al 2009;Fuiman and Ojanguren 2011;Olin et al 2012;Andree et al 2015). We observed positive correlations between fatty acid complexity of individual females and the quality eggs they produced, as determined by egg size, lipid content, and egg size variability, suggesting that females with more complex fatty acid profiles produced higher-quality eggs.…”
Section: R a F Tmentioning
confidence: 65%
“…However, spawning stock biomass alone is often a poor predictor of reproductive potential for many fish species (Leggett and Frank, 2008), and recent research has suggested that the composition of the spawning stock probably plays a role. Incorporating the size and/or age composition of the spawning stock into recruitment models appears to improve their predictive power (Forbes and Peterman, 1994;Marteinsdottir and Thorarinsson, 1998;Murawski et al, 2001) possibly because various aspects of reproductive effort (e.g., quantity and quality of gametes, spawning time and location) are related to adult age and body size (Mousseau and Fox, 1998;Berkeley et al, 2004;Green, 2008;Venturelli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%